REVITALISASI EVALUASI DALAM PEMBELAJARAN DI SEKOLAH - Agus Jayadi; M. Ary Irawan (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2022)
This study uses a literature study by reviewing several books and thoughts of the characters. The researcher discusses the evaluation of learning both in terms of epistemology, terminology, axiology, and ontology. Evaluation can be interpreted as an effort made to determine the level of success and weakness of a learning process, which includes all the components in it to achieve certain goals. Learning evaluation aims to improve and optimize learning activities which are later expected to improve student learning outcomes. In the implementation process, the evaluation must apply several principles, techniques and procedures that must be followed for the good results to be obtained. In addition, in the evaluation it is necessary to pay attention to several principles such as objectivity, continuity, and comprehensiveness or overall.